2016
DOI: 10.7863/ultra.15.08023
|View full text |Cite
|
Sign up to set email alerts
|

On the Physical Basis of Pulmonary Sonographic Interstitial Syndrome

Abstract: ung sonography is widely accepted and used in emergency medicine and critical care. [1][2][3][4][5] Moreover, many pulmonologists are interested in chest sonography for the study of pleural diseases and are increasingly discovering a role for sonography in parenchymal lung diseases. [6][7][8][9] For those physicians who are devoted to chest sonography, a clear dichotomy between usual sonography and aerated tissue sonography is obvious. Pleural sonography is effective under most circumstances, whereas lung sono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 41 publications
4
133
0
5
Order By: Relevance
“…This highly scattering environment can explain this peculiar pattern. 3,5,7 • Score 3: The scanned area shows dense and largely extended white lung with or without larger consolidations.…”
Section: Scoring Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This highly scattering environment can explain this peculiar pattern. 3,5,7 • Score 3: The scanned area shows dense and largely extended white lung with or without larger consolidations.…”
Section: Scoring Proceduresmentioning
confidence: 99%
“…A decade of clinical [1][2][3][4] and physical studies [5][6][7][8][9] clearly showed that lung ultrasound (LUS) is able to detect interstitial lung disease, subpleural consolidations, and acute respiratory distress syndrome from any etiologic cause. New evidence from published studies, [10][11][12] national and international organization statements, and informal case discussions with internationally recognized experts are showing the usefulness of LUS for the management of patients with 2019 new coronavirus disease (COVID-19) pneumonia, from diagnosis to monitoring and follow-up.…”
mentioning
confidence: 99%
“…Specifically, to evaluate the progression of the pathology, a 4-level scoring system was devised [32], with scores ranging from 0 to 3. Score 0 indicates the presence of a continuous pleural-line accompanied by horizontal artifacts called A-lines [33], which characterize a healthy lung surface. In contrast, score 1 indicates the first signs of abnormality, i.e., the appearance of alterations in the pleural-line in conjunction with vertical artifacts.…”
Section: Iclus-db: Data Collection and Annotationmentioning
confidence: 99%
“…The physical basis of our observations are well described. 5 Figure 4A); LUS detected the basal consolidation with air inside, suspected for a small cavernae although not specific (4B). CT, computed tomography; LUS, lung ultrasound the pleural line and generically defining the "sonographic interstitial syndrome", a nonspecific pattern associated to numerous conditions and still not well understood).…”
Section: Chest Ultrasound Findings In Children With Confirmed Pulmonamentioning
confidence: 99%